Islamic resurgence, politics and economics in contemporary Egypt - Heinrich, Hans Georg (Zeitschrift für Afrikastudien, 1989)
The authors explain the various Islamic currents in Egypt against the background of the political culture and the collective memory of the Egyptian society. They argue that it is not Islam that changes the Egyptian society but conversely, that the needs, aspirations and problems of contemporary Egypt are reflected in the various currents. (DÜI-Hns)